Online Registration Information System at Imelda Medan Kindergarten/PAUD - Tanjung, Rita Yanti; Rajagukguk, Denni M. (Devitara Innovations, 2023)
Computers are very well known and have been widely used by the public. Even with a computer system, this can complete all the work that has been done manually. With the help of computers the work can be completed quickly and structured. Computers are tools that are very popular today in solving problems that are used in various fields of science and information technology. With the development of this information technology, an Advocacy Information System and KIE (Information and Education Communication) at the North Sumatra BKKBN were made on a Web-based basis by creating a database to obtain information which is still being done manually. The Advocacy Information System and KIE (Information and Education Communication) at the North Sumatra BKKBN can be done using several programming languages including mysql. The ability to process data is very important for the Web-based Advocacy Information System and KIE (Information and Educational Communication) at the North Sumatra BKKBN which is engaged in information and moderator. The Advocacy Information System and IEC (Information and Education Communication) at the North Sumatra BKKBN still uses manual work so it requires changes that help researchers to complete work effectively and efficiently. That's why the author made a Web program that serves to provide information to the public about family planning that has been established, to make it easier for people to get information about family planning.